Pola Pemasaran Produksi Padi Lahan Pasang Surut di Kabupaten Banyuasin Sumatera Selatan - Riswani Riswani; Yunita Yunita; Elly Rosana; Trisnawati Trisnawati (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2014)
Banyuasin district is one of the rice producing regions in South Sumatra which rely on sub-optimal land type with category tidal land to produce rice production. The statistical data showed that Banyuasin District is a region that produces the highest rice production of rice-producing areas in South Sumatra. However, the high level of production is not able to guarantee farmers' income is also high, and prices at the consumer level will be low. This is because rice prices received by farmers is still relatively quite low. The condition is the main attraction of researchers to conduct this research with the aim to analyze the pattern of marketing tidal swamp rice production through the analysis of marketing channels, marketing margins, marketing efficiency level and method of pricing of each institution tidal swamp rice marketing in the District Banyuasin This study was conducted in District Rambutan Banyuasin Regency, with time data collection in April-May 2014. The results showed that there are two groups of marketing channels tidal swamp rice production in the district which are both classified as Banyuasin indirect marketing channels. Pricing method of rice is determined by the merchant so that farmers are recipients of the price (price taker) while marketing agency is a price maker. The calculation of the value of marketing margins in both marketing channel marketing agency in each figure shows the range varies with Rp.400 per kg to Rp, 3,100, - per kg. The analysis shows that the pattern of marketing efficiency marketing tidal swamp rice production is already relatively efficient, with the highest levels of efficiency are the major traders.